2018
DOI: 10.1097/md.0000000000012026
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term outcomes of liver transplantation using moderately and severely steatotic donor livers

Abstract: The use of moderately and severely steatotic livers is associated with unfavorable short-term outcomes, but long-term outcomes are relatively less influenced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 56 publications
0
21
0
3
Order By: Relevance
“…Wu et al recently performed a systematic review and found organs with moderate steatosis had increased risk of PNF but no difference in 1-year mortality. [25] The results of our study show that risk is not evenly distributed across the range of moderate MaS. While we found increased risk of 30-day graft loss for multiple levels of MaS, the likelihood for long- https://doi.org/10.1371/journal.pone.0230995.g003…”
Section: Plos Onementioning
confidence: 55%
“…Wu et al recently performed a systematic review and found organs with moderate steatosis had increased risk of PNF but no difference in 1-year mortality. [25] The results of our study show that risk is not evenly distributed across the range of moderate MaS. While we found increased risk of 30-day graft loss for multiple levels of MaS, the likelihood for long- https://doi.org/10.1371/journal.pone.0230995.g003…”
Section: Plos Onementioning
confidence: 55%
“…Fat droplets in small droplet steatosis are not large enough to displace the nucleus; this finding is often inaccurately reported as being microvesicular steatosis on biopsy. Although both small and large droplet steatosis contribute to overall macrovesicular steatosis, historically small droplet macrovesicular steatosis and microvesicular steatosis were used synonymously, resulting in ongoing confusion [3]. We hypothesize that some of the observed differences in post-LT AKI between otherwise similarly-appearing steatotic grafts might be related to this histological variation.…”
Section: Discussionmentioning
confidence: 96%
“…Primary nonfunction, poor early graft function, and decreased patient and allograft survival have all been associated with the use of steatotic liver allografts for transplantation [1][2][3]5]. This, combined with inaccurate and inconsistent reporting of liver allograft biopsies, has led to a high discard rate of grafts with moderate (>30%) steatosis [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in the setting of macrovesicular steatosis, two types of fat droplets are seen, small droplets and large droplet. Fat droplets in small droplet steatosis are not large enough to displace the nucleus, and often this finding is misreported in the literature as being microvesicular steatosis on biopsy leading to confusion [9]. We suspect these differences in the reporting may have affected the moderate disagreement in the assessment of the degree of macro-steatosis among the internal and external (procurement site) pathologist.…”
Section: Plos Onementioning
confidence: 98%